2020
DOI: 10.1089/jpm.2019.0342
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Technologies for Continuous Monitoring of Cancer Patients in Palliative Care Aiming to Predict Health Status Deterioration: A Feasibility Study

Abstract: Background: Unplanned readmissions or emergency visits (EVs) after discharge from hospital are frequent in patients in palliative care. Strategies to anticipate and prevent rapid deterioration of health are needed. Objective: Assessing feasibility and predictive ability of remote monitoring using wearables. Design: Prospective observational feasibility study in a single center. Setting/Subjects: Thirty cancer patients with an estimated life expectancy of >8 weeks to <12 months, aged >18 years and being dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 46 publications
1
70
0
Order By: Relevance
“…In a sample of 10 gynecologic cancer patients, Fitbit and smartphone sensor data were actively monitored for anomalies; this led the research team to identify a patient with severe nausea and vomiting whose symptoms were then able to be managed over the phone as well as a patient who took fewer steps and spent less time away from home prior to an emergency department visit 46 . Finally, a recent study collected both smartphone and wearable sensor data as well as patient-reported pain and distress ratings and quality of life measures in 25 palliative cancer patients 47 . Mobile sensor data were significantly correlated with pain and distress ratings.…”
Section: Smartphone Sensors In Oncology Researchmentioning
confidence: 99%
“…In a sample of 10 gynecologic cancer patients, Fitbit and smartphone sensor data were actively monitored for anomalies; this led the research team to identify a patient with severe nausea and vomiting whose symptoms were then able to be managed over the phone as well as a patient who took fewer steps and spent less time away from home prior to an emergency department visit 46 . Finally, a recent study collected both smartphone and wearable sensor data as well as patient-reported pain and distress ratings and quality of life measures in 25 palliative cancer patients 47 . Mobile sensor data were significantly correlated with pain and distress ratings.…”
Section: Smartphone Sensors In Oncology Researchmentioning
confidence: 99%
“…PROs were added to this table when used in 3 or more papers. In this review, the most commonly used validated PRO questionnaire for collecting HRQoL data is the EORTC QLQ-C30, used in 28% of the 50 included papers [10][11][12][13][14][15][16][17][18][19][20][21][22]. It is a European widely used core generic questionnaire for cancer patients, and comprises most dimensions of wellbeing as described by Linton et al [6], excluding spiritual wellbeing and personal circumstances.…”
Section: Patient Reported Outcomesmentioning
confidence: 99%
“…Several PRO questionnaires were used to collect data regarding patient reported symptoms. The EORTC QLQ-cancer specific modules were used to collect cancer-specific patientreported symptoms in 7 out of 50 included papers [6,7,13,14,17,20,21]. These modules are specific to tumour site, treatment modality, or a HRQoL dimension, to be administered in addition to the core questionnaire (EORTC QLQ-C30) [39].…”
Section: Patient Reported Outcomes: Symptomsmentioning
confidence: 99%
See 2 more Smart Citations